Modi 3.0: Bigger, Higher, Stronger - Bhandari, Pradeep (Noida Om books international, 2024)
The results of Assembly elections held in Chhattisgarh, Madhya Pradesh and Rajasthan in December 2023 provided a big boost to the Bharatiya Janata Party. They confirmed what is common knowledge: as far as the 2024 parliamentary elections are concerned, the BJP remains firmly in pole position. With the 18th Lok Sabha elections around the corner, the Jan Ki Baat$1 (Bs team with an unmatched track record of predicting election results has been racing through constituencies conducting public opinion polls and pre-election surveys for the forthcoming elections. The polls re-establish that Prime Minister Narendra Modi$1 (Bs popularity remains intact. The fragmented Opposition remains no match to India$1 (Bs most admired leader, most invincible political organization and most savvy marketing machinery. In Modi 3.0, renowned psephologist, journalist and bestselling author Pradeep Bhandari provides an incisive and in-depth account of how India votes and why Narendra Modi remains unchallenged and will return with a bigger, higher and stronger mandate.s
Keywords: Prime minister; Indian Politics